A revision of the Afrotropical hover fly genus Afroxanthandrus Kassebeer, 2000 (Diptera, Syrphidae), with the description of two new species and one new synonymy - Midgley, J.M.; Goergen, G.; Jordaens, K. (Museum National D'Histoire Naturelle, 2024)
The hover fly (Diptera: Syrphidae) genus Afroxanthandrus Kassebeer, 2000 is revised based on morphological and molecular characters. Two new species, Afroxanthandrus comorosensis sp. nov., and Afroxanthandrus conopeum sp. nov. are described, while Xanthandrus magnificus Thompson, 2019 is a new junior synonym of Afroxanthandrus congensis (Curran, 1938). We also redescribe A. congensis stat. rev. and A. longipilus stat. rev. and report additional distribution records for both species.